Willingness to pay for social health insurance among informal sector workers in Wuhan, China: a contingent valuation study - Zhang Xinping; Liu Yuanli; Bärnighausen Till; Sauerborn Rainer (BMC, 2007)
Abstract Background Most of the about 140 million informal sector workers in urban China do not have health insurance. A 1998 central government policy leaves it to the discretion of municipal governments to offer informal sector workers in cities voluntary participation in a social health insurance for formal sector workers, the so-called 'basic health insurance' (BHI). Methods We used the contingent valuation method to assess the maximum willingness to pay (WTP) for BHI among informal sector workers, including unregistered rural-to-urban migrants, in Wuhan City, China. We selected respondents in a two-stage self-weighted cluster sampling scheme. Results On average, informal sector workers were willing to pay substantial amounts for BHI (30 Renminbi (RMB), 95% confidence interval (CI) 27-33) as well as substantial proportions of their incomes (4.6%, 95% CI 4.1-5.1%). Average WTP increased significantly when any one of the copayments of the BHI was removed in the valuation: to 51 RMB (95% CI 46-56) without reimbursement ceiling; to 43 RMB (95% CI 37-49) without deductible; and to 47 RMB (95% CI 40-54) without coinsurance. WTP was higher than estimates of the cost of BHI based on past health expenditure or on premium contributions of formal sector workers. Predicted coverage with BHI declined steeply with the premium contribution at low contribution levels. When we applied equity weighting in the aggregation of individual WTP values in order to adjust for inequity in the distribution of income, mean WTP for BHI increased with inequality aversion over a plausible range of the aversion parameter. Holding other factors constant in multiple regression analysis, for a 1% increase in income WTP for BHI with different copayments increased by 0.434-0.499% (all p < 0.0001), and for a 1% increase in past health care expenditure WTP increased by 0.076-0.148% (all p < 0.0004). Being male, a migrant, or without permanent employment significantly decreased WTP for BHI. Education was not a significant determinant of WTP for BHI. Conclusion Our results suggest that Chinese municipal governments should allow informal sector workers to participate in the BHI. From a normative perspective, BHI for informal sector workers is likely to increase social welfare because average WTP for BHI is significantly higher than estimates of the average cost of BHI. We further find that informal sector workers do not value the BHI as a mechanism to recover the relatively frequent but small financial losses associated with common illnesses, but because it protects against the rare but large financial losses associated with catastrophic care. From a behavioural perspective, our results predict that at a price equal to the average premium contribution of formal sector workers 35% of informal sector workers will enrol in the BHI. Subsidies and changes in insurance attributes (e.g. including catastrophic care and portability) should be effective in increasing BHI coverage. In addition, coverage should expand with rising incomes among informal sector workers in China. Finally, adverse selection will be unlikely to be a large problem, if the BHI is offered to informal sector workers.